The role of Th17 lymphocytes in pathogenesis of autoimmune arthritides - Pogoda, Katarzyna; Pyszniak, Maria; Bańka, Magdalena; Rybojad, Beata; Tabarkiewicz, Jacek (Polish Journal of Public Health, 2014)
Th17 cells are newly described population of lymphoctyes, that recruits neutrophils to the site of inflammation and activate inflammatory phenotype of various tissues. They also play a pivotal role in autoimmune diseases and cancers. These cells secrete mainly different isoforms of IL-17, but also IL-21 and IL-22. Rheumatoid arthritis and juvenile idiopathic arthritis are the most common autoimmune joints’ inflammatory disease, affecting respectively adults and children. For a long time the immunopathogenesis of autoimmune diseases has been associated with Th1 lymphocytes. This hypothesis has changed after the discovery of Th17 cells, which are thought to be key mediators of autoimmune arthritides.